Relacja między przepływami środków pieniężnych a stopą dyskonta w ocenie efektywności inwestycji - Słoński, Tomasz (The Relation Between Cash Flows and Discount Rate in Investment Appraisal Process, 2005)
Among many different methods of the investment valuation the DCF method is the most preferable. The project's cash flow can be identified in different ways depending on financial flow treatment. This paper describes the linkage between three methods of cash flow estimation (NPV, APV, Equity DCF) and their appropriate discount rates.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 394-404